2008
DOI: 10.1080/00423110701271864
|View full text |Cite
|
Sign up to set email alerts
|

Full vehicle simulation using thermomechanically coupled hybrid neural network shock absorber model

Abstract: In the case of full vehicle models, the technique of multi-body simulation (MBS) is frequently used to study their highly non-linear dynamic behaviour. Many non-linearities in vehicle models are induced by force elements like springs, shock absorbers, bushings and tires. Commonly, spline functions are used to represent the force responses of these components. If the non-linear relationships are more complicated, the spline approximations are no more accurate. An alternative approach is based on empirical neura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…In previous scientific research, shock absorber tests results could be found that take into account temperature [5,10,14,18] and their impact on the driving comfort of the user [13]. Studies of the shock absorbers filled with numerous types of fluids were also presented in [12], where the authors presented their heating characteristics during operation with a constant amplitude and frequency.…”
Section: Highlights Abstractmentioning
confidence: 99%
“…In previous scientific research, shock absorber tests results could be found that take into account temperature [5,10,14,18] and their impact on the driving comfort of the user [13]. Studies of the shock absorbers filled with numerous types of fluids were also presented in [12], where the authors presented their heating characteristics during operation with a constant amplitude and frequency.…”
Section: Highlights Abstractmentioning
confidence: 99%
“…Due to high demanding for comfort of automobiles, the suitable design of the hydraulic shock absorber becomes very important (Faraj, Holnickiszulc, & Knap, 2016). Hydraulic shock absorber is an important part of vehicle suspension and steering system (Preda, 2016), it reduces the vibration between the wheel and the car main body through the damping force generated by the internal throttle slice (Yu, Ye, & Wang, 2011), and it can also alleviate the vibration and impact of the car main body caused by uneven road surface, which can improve comfort of the vehicle ride (Pracny, Meywerk, & Lion, 2008). However, the hydraulic shock absorber will be aged if it works for a long time in an environment with strong vibration impact and large temperature change (Dong, Yu, & Yang, 2016) and the inner part of the hydraulic shock absorber will circulate to generate high-pressure and low-pressure area.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] In Holzmann et al, 14 they used a radial basis function network to compensate influences of changing road conditions on parameters of an analytic simulation model. Moreover, Pracny et al 15,16 developed a shock absorber model based on the coupling of a neural network and a spline function. Next to its accurate modelling capabilities as shown in the above-mentioned areas, hybrid models require fewer training samples which make them easier to adapt to parametric changes.…”
Section: Introductionmentioning
confidence: 99%